1991
DOI: 10.1099/00207713-41-3-451
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for a New Family, Campylobacteraceae

Abstract: The genera Campylobacter, Arcobacter, Helicobacter, Wolinella, and "Flexispira" constitute, within the class Proteobacteria, a separate eubacterial lineage identified as rRNA superfamily VI. A considerable number of common genotypic and phenotypic features differentiate the genera Campylobacter and Arcobacter from the other members of this group. Therefore, we propose that the genera Campylobacter and Arcobacter should be included in a separate family, for which the name Campylobacteraceae is proposed.The bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
114
1
5

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(123 citation statements)
references
References 34 publications
2
114
1
5
Order By: Relevance
“…Further, the three Campylobacter groups had a 49.3% overall 16S rRNA sequence similarity to representatives of the alpha, beta, and gamma phylogenetic branches of the class Proteobacteria, a depth of divergence greater than that among the three branches themselves and consistent with the conclusions reached by Romaniuk et al (50). Stackebrandt et al (54) took the position that overall there was a meaningful affinity between the campylobacters and members of the class Proteobacteria, and Vandamme et al (61,62) concluded that while the campylobacters clearly constitute a sixth rRNA superfamily within the gram-negative bacteria and are equally removed from all subclasses within the class Proteobacteria, it seems appropriate to consider rRNA superfamily Vl a fifth subclass of the class Proteobacteria, as deduced from a suggestion of Murray et al (33).…”
Section: Discussionsupporting
confidence: 72%
“…Further, the three Campylobacter groups had a 49.3% overall 16S rRNA sequence similarity to representatives of the alpha, beta, and gamma phylogenetic branches of the class Proteobacteria, a depth of divergence greater than that among the three branches themselves and consistent with the conclusions reached by Romaniuk et al (50). Stackebrandt et al (54) took the position that overall there was a meaningful affinity between the campylobacters and members of the class Proteobacteria, and Vandamme et al (61,62) concluded that while the campylobacters clearly constitute a sixth rRNA superfamily within the gram-negative bacteria and are equally removed from all subclasses within the class Proteobacteria, it seems appropriate to consider rRNA superfamily Vl a fifth subclass of the class Proteobacteria, as deduced from a suggestion of Murray et al (33).…”
Section: Discussionsupporting
confidence: 72%
“…Arcobacter spp. are often microaerophilic (Vandamme and Deley, 1991) and growth in the oysters could be facilitated by periodical valve closing (Sow et al, 2011) or high variation in respiratory time activity (Bougrier et al, 1998)-both of which may promote microaerophilic conditions. Dominance of Arcobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…Within well-characterized genera, differences in melting temperatures [T,(,)] for the most part range from 4 to 7°C (7), whereas differences in T+) values of up to 12°C are found within bacterial families (32). This implies that, except for F. odoratum, all members of the four natural groups sensu Holmes (13) should be excluded from the genus Flavobacterium on genotypic grounds, as the name Flavobacterium must be retained for the type species.…”
mentioning
confidence: 99%